Experience of Formation and Implementation of the Regional Program of Immunization of Children's Population of St. Petersburg against Papillomavirus Infection - A. S. Simakhodsky; M. F. Ippolitova (Эпидемиология и вакцинопрофилактика, 2019)
An integrated approach to maintaining reproductive health includes, among other things, primary prevention of cervical cancer and other diseases associated with the human papillomavirus. Girls 11-14 years old vaccination against human papillomavirus is a priority in the fight against HPV-associated diseases. The purpose of the work is to show the methodology of legal support for the formation and implementation of the HPV vaccine prevention program, which is not included in the National Vaccination Calendar, using the example of the system, institutions and services aimed at protecting the reproductive health of children and adolescents in St. Petersburg.Materials and methods. Primary specific prophylaxis of HPV-associated diseases was carried out by certified vaccines: bivalent -for protection against HPV types 16 and 18, and tetravalent - for types 6, 11, 16, 18. Information on vaccination was included in the certificate of preventive vaccinations, form No. 156/у- 93 A6. Determining the size of contingents to be vaccinated, taking into account the prevalence of infectious diseases was carried out according to the statistical forms: No. 30 «Information about the medical organization», No. 2 «Information about infectious and parasitic diseases», No. 5 «Information about preventive vaccinations».Results. From 2012 to 2014, 22,548 girls between the ages of 12 and 14 years of age (13% of the subject) were covered by vaccination; from 2015 to 2018, 13,062 girls (7.5% of the subject) were covered. First of all, girls who are on full state support and are at risk (from families with an oncologic history) were vaccinated. From 2015, young woman under 17 years old began to be vaccinated. The planned coverage in 2019 will be 9.2% of the population to be immunized. All vaccinated were patients of children's city polyclinics.Conclusion. The world practice of using vaccination against oncogenic viruses has proven its effectiveness against human papillomavirus infection. Before deciding on the inclusion of vaccines against HPV infection in the National Schedule of Vaccines, the health authorities of the constituent entities of the Russian Federation should actively look for opportunities to form and implement regional vaccination programs. We have shown one of the possible ways. The current favorable conditions for the development of maternal and child health services contribute to the inclusion of vaccination against HPV infection in the immunization schedules of the constituent entities of the Russian Federation.